2016
DOI: 10.1007/s00431-016-2723-9
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric pre-hospital emergencies in Belgium: a 2-year national descriptive study

Abstract: • Pediatric and adult emergencies differ. • Pediatric life-threatening emergencies are not frequent. What is New: • This study is the first to describe a European national cohort of pediatric physician-staffed EMS missions and to compare the pediatric and the adult missions at a national level. • This large cohort study confirms scarce regional data indicating that pediatric pre-hospital emergencies are not frequent and mostly non-life-threatening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
8
9
0
Order By: Relevance
“…The dispatch codes presented in Additional file 2 suggest that many of the issues classified according to this category concerned breathing problems. This is consistent with previous findings, as respiratory problems seem to be a common cause for emergency medical service activation [ 15 17 , 20 ]. However, the prevalence of calls concerning breathing problems in our study seems slightly lower than previously reported.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The dispatch codes presented in Additional file 2 suggest that many of the issues classified according to this category concerned breathing problems. This is consistent with previous findings, as respiratory problems seem to be a common cause for emergency medical service activation [ 15 17 , 20 ]. However, the prevalence of calls concerning breathing problems in our study seems slightly lower than previously reported.…”
Section: Discussionsupporting
confidence: 93%
“…Almost 7% of the calls managed by the EMDC during the study period concerned paediatric patients. This is comparable to findings in other studies [ 15 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Reporting of airway training was too heterogeneous to support an analysis however. Some studies provided no description of training [19,21,24,26,39,44,45], and some reported pooled data from multiple agencies [3,28,32], whilst others described the studied teams simply as Advanced Life Support and/or Paediatric Advanced Life Support certified [5,20,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%